In memoriam: Emajuddin Ahmad - Hasan, Md. Mahmudul (Media New Age Ltd., 2021)
Nowadays, we often come across unpleasant media reports involving vice-chancellors of various universities in Bangladesh. They reportedly unleash musclemen in the guise of student activists to crush legitimate movements of ordinary students. Academic administrators’ desire to exercise political power at the expense of academic traditions have worsened campus climate around the country. This makes us nostalgic of times gone by when political links of the vice-chancellors were less evident and they were not keen on unleashing assailants to suppress dissent, limit ordinary students’ freedom of expression or disrupt their peaceful gatherings. On 17 July 2020, professor Emajuddin Ahmad passed away at the age of 87. It was not a premature death. However, we hope that we will have considerate vice-chancellors like him who will retain the dignity of their chair and will not debase it by their anti-academic behaviours.